2011
DOI: 10.1186/1477-7827-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Members of the murine Pate family are predominantly expressed in the epididymis in a segment-specific fashion and regulated by androgens and other testicular factors

Abstract: BackgroundSpermatozoa leaving the testis are not able to fertilize the egg in vivo. They must undergo further maturation in the epididymis. Proteins secreted to the epididymal lumen by the epithelial cells interact with the spermatozoa and enable these maturational changes, and are responsible for proper storage conditions before ejaculation. The present study was carried out in order to characterize the expression of a novel Pate (prostate and testis expression) gene family, coding for secreted cysteine-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
6
20
0
Order By: Relevance
“…Many genes exhibit cell type and segment-specific expression patterns, where expression can be restricted to one particular subsegment. Additionally, several gene families, for example, prostate and testis expression (Pate, Turunen et al 2011) and wingless-type MMTV integration site family (Wnt, Koch et al 2015), display distinct expression patterns along the tissue; certain family members are restricted to specific epididymal regions, whereas other members are present in the whole tissue (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Many genes exhibit cell type and segment-specific expression patterns, where expression can be restricted to one particular subsegment. Additionally, several gene families, for example, prostate and testis expression (Pate, Turunen et al 2011) and wingless-type MMTV integration site family (Wnt, Koch et al 2015), display distinct expression patterns along the tissue; certain family members are restricted to specific epididymal regions, whereas other members are present in the whole tissue (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm maturation is facilitated by a number of proteins secreted by the epididymal epithelial cells into the luminal fluid, which then bind on to the sperm surface (Ducheux et al, 2003). Defensins (Yenugu et al, 2004(Yenugu et al, , 2006Travis et al, 2000), members of the sperm-associated antigen 11 family (Hamil et al, 2000), lysozymes Mandal et al, 2003), lipocalins (Hamil et al, 2003), cathelicidins, protease inhibitors Blankenvoorde et al, 1998;Hiemstra et al, 1996), inhibitors of complement lysis (Collard and Griswold, 1987;Griswold et al, 1986), the cysteine-rich proteins such as CRISPs (Jalkanen et al, 2005;Luo et al, 2012), and members of the prostate-and testis-expressed (PATE) family (Bera et al, 2002;Soler-Garcia et al, 2005;Levitin et al, 2008;Turunen et al, 2011) are some examples of a wide range of proteins that bind to the sperm surface . Further, a variety of factors secreted by the seminal vesicles and prostate also aid in the formation of functional http://dx.doi.org/10.1016/j.jri.2015.02.009 0165-0378/© 2015 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…In the human and mouse, the Pate gene cluster is present on chromosomes 11 and 9 respectively (Levitin et al, 2008;Bera et al, 2002;SolerGarcia et al, 2005;Turunen et al, 2011). Although the Pate genes were initially thought to be prostate-and testisspecific, a recent study indicated their expression in the epididymis and not in the testis and prostate (Turunen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations